PENGARUH TEKANAN EKSTERNAL, KOMITMEN MANAJEMEN, KETIDAKPASTIAN LINGKUNGAN, GAYA KEPEMIMPINAN, DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Survei Pada Satuan Kerja Perangkat Daerah Pemerintah Kabupaten Pelalawan) - Lia Andriyani; Emrinaldi Nur DP; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to test the influence of external pressures, environmental uncertainty, management commitment, leadership style, and accessibility of the financial statements for the application of the transparency of financial reporting. The location of this research is a unit of Work of regional Government of Pelalawan Device. The technique of collecting samples in this research is done by using a purposive sampling method with the total sample as much as 64 respondents. Types and sources of data are the primary and secondary data. Methods of data analysis done with test of normality, validity, reliability, multikolinieritas, heteroscedastisity, autocorrelation. This research hypothesis testing using multiple linear regression analysis. Test tools top of hypothesis test is a test t, F and the coefficients of determination (R2). The tools used were SPSS statistics version 20.00. The results showed that variable of external pressure (1,7%), management commitment (2,5%), environmental uncertainly (20,2%), leadership style (1%), accessibility the financial statements (9%).Keywords : Transparency, External Pressure, Management Commitment, and Accessibility.